The Experience of Denmark in Working with Preschool Children: What Can Ukraine Learn? - Ponomarenko, Aliona; Yuryeva, Kateryna (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The relevance of this research is driven by the necessity to study the educational experience of European countries for creative utilization in the process of integrating Ukraine’s education system into the European and global educational and scientific space, as well as by Denmark’s high social standards, consistently leading the global happiness rankings for many years. The aim of this research is to outline the main theoretical and methodological ideas and practical approaches to organizing work with preschool children in Denmark for comparison with the traditional approaches in Ukraine. The research methodology included analysis of comparative pedagogical literature, publications in the Danish educational press, observations in Danish educational institutions, conversations, and interviews with parents of preschool children – both Danish citizens and Ukrainians seeking temporary protection in this country. The results revealed significant differences in the experiences of Ukraine and Denmark regarding work with preschool children: less regulation of daily routines in Danish educational institutions; a focus primarily on the interests and development of the children rather than preparation for school education; an emphasis on cooperation, mutual assistance, and empathy in Danish child institutions with almost no competitiveness among Danish children, and so on. The conclusions outline the prospects for further research to uncover the underlying reasons for the identified differences. In particular, it is considered appropriate to study the impact on the organization of work with preschool children of the traditional Danish worldview, known as hygge, as well as the somewhat lesser-known phenomenon – the so-called Law of Jante.